Inovasi Elektrostimulator Berbasis Arduino: Solusi Sederhana untuk Eksperimen dan Aplikasi Medis - Arianto, Eko; Dwi Susanto (J-Innovation, 2024)
Electrostimulation has become a widely utilized method in various fields, such as medicine, sports, and research, to stimulate biological tissues using electrical currents of specific frequencies. However, commercially available electrostimulation devices are often expensive and complex, making them less accessible for educational purposes or researchers with limited budgets. This study aims to develop a simple Arduino-based electrostimulator capable of generating sinusoidal waves with adjustable frequency and amplitude. The device was designed using PWM signals from Arduino filtered through an RC circuit to produce smooth sinusoidal waves, which were then amplified using transistors and stepped up in voltage through a step-up transformer. Testing demonstrated that the device could generate stable sinusoidal waves with frequencies of up to 600 Hz. Trials on human skin revealed varying sensations, ranging from mild vibrations to muscle contractions, depending on the frequency applied. This research highlights the potential of an Arduino-based electrostimulator as a cost-effective and flexible alternative for educational and research purposes, as well as for exploring the effects of electrostimulation. With its simple design, the device can be further developed for various medical and scientific applications in the future.